Factors that contribute to intention to make fraud claim at Social Security Organization (SOCSO) / Wan Khariah Alwi - Alwi, Wan Khariah (2010)
Fraud has increased considerably over the recent years, and professionals believe this trend is likely to continue. So that this research is to determine the factors that contribute to the intention to make fraud claim at Social Security Organization (SOCSO). As an introduction stage of the research, researcher briefly explains about the background of this study and the problem statements. The researcher will include the literature review in chapter two, which are the past research that purposely uses to support the researcher theoretical framework. Based from past research the variable that is relating to the intention’s factors of contributor to make the fraud claim at Social Security Organization (SOCSO). The independent variable adapt from past research, are opportunities to commit fraud, situational pressures on the individual and personal integrity. Research methodology and design explains the way on how the researcher gathers data and information while conducting the research. It is an important stage in research process because this stage will give the researcher the ideas and assumptions to clarify the objectives, problem statement and research questions. In this research, the researcher will use one method of gathering data, which is primary data. The researcher made interpretations based on the results of the survey to see if the research objectives have all been met. The sample size comprises 100 respondents which are contributor of SOCSO. The last chapter in a research, which includes the recommendation and conclusion of the research, the recommendation shows the way to overcome problem or develop new ways to strengthen the weakness of the organization. In this research context, is to improve awareness of Social Security Organization (SOCSO) towards the intention to make fraud claim among the contributor. Conclusion is a summarize of finding, which include the answer to the research question and research objective.